A Matlab Tool for Morris Water Maze Test Implementation - Yavuzkilic, Semih; Aslan, Muzaffer; Sengur, Abdulkadir (Ieee, 2018)
Morris water maze (MWM) is a behavioral test used to study in spatial learning and memory with laboratory mice and rats. This test has a tank filled with water and a hidden platform inside the tank. The location of this platform is fixed throughout the test. The ability of the mice or rats to locate platform and their position depends on the movement of these animals in the maze. The training procedures characteristics, the water characteristics, (temperature, purity, etc.) the livestock feeding status of the test animals and many other variables affect the performance of the MWM. A direct analysis performed by the investigator will cause a lot of behavioral information loss, so animal performance is recorded through by a camera during the experiment as well. In this study, by using Matlab, MWM test was performed. In the first step of the analysis, the location of the maze is determined by using a thresholding algorithm. After determining the location of the maze, Region of Interests (ROI) are defined. Then, location of mouse is detected for each video frame by segmentation of maze. The maze is divided into four sections virtually to better analyze the behavior of the mouse. The time spent in each section and orbits which is drawing by mouse are recorded.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Morris Water Maze; Image Processing; Segmentation